Takotsubo syndrome in hemodynamically unstable patients admitted to the intensive care unit – a retrospective study. Issue 8 (18th July 2017) - Oras, J.; Lundgren, J.; Redfors, B.; Brandin, D.; Omerovic, E.; Seeman‐Lodding, H.; Ricksten, S.‐E.
Abstract : Introduction: Takotsubo syndrome (TS) is an acute cardiac condition that is often triggered by critical illness but that has rarely been studied in the intensive care unit (ICU) setting. The aim of this study was to (i) estimate the incidence of TS in a hemodynamically unstable ICU‐population; (ii) identify predictors of TS in this population; (iii) study the impact of TS on prognosis and course of hospitalization. Methods: Medical records from all patients admitted to our general ICU from 2012 to 2015 were analyzed. TS was defined as having transient regional wall motion abnormalities (RWMA) with a typical pattern not attributable to a history of coronary artery disease or acute coronary syndromes. Results: Out of 6470 patients admitted to the ICU, echocardiography due to hemodynamic instability was performed in 1051 patients; 467 had LV dysfunction and 59 fulfilled TS criteria. Patients with TS had higher SAPS 3 scores on admission than patients with normal LV function. Septic shock, cardiac arrest, cerebral mass lesion, female sex and low pH were independently associated with TS on admission. Patients with TS needed more ICU resources measured by higher NEMS scores and longer ICU‐stay. Crude mortality was higher in TS patients (32%) vs the ICU‐population (20%, P = 0.020), but there were no differences in a SAPS 3 adjusted analysis. Conclusion: TS was not an uncommon cause of LV dysfunction in hemodynamically unstable ICU‐patients. Furthermore, TS was associated with a more complex disease. TS is a complication to take in consideration in the critically ill.